Recent Publications (Quarterly Journal of Economics, 1940)
Recent Publications Get access The Quarterly Journal of Economics, Volume 54, Issue 4_Part_1, August 1940, Pages 696–699, https://doi.org/10.1093/qje/54.4_Part_1.696 Published: 01 August 1940